2024
DOI: 10.1101/2024.03.20.581580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery and chemical optimisation of a Potent, Bi-cyclic (Bicycle®) Antimicrobial Inhibitor ofEscherichia coliPBP3

Catherine E. Rowland,
Hector Newman,
Tazmin T. Martin
et al.

Abstract: Penicillin binding proteins (PBPs) are well validated antimicrobial targets, but the prevalence of β-lactamase driven resistance and, more rarely, target-based mutations, necessitates new classes of PBP-targeting drugs. Here we describe the discovery and optimisation of novel, bicyclic peptide (Bicycle®) inhibitors of E. coli PBP3 (EcPBP3) using a proprietary phage display platform, and their conjugation to linear antimicrobial peptides to confer outer membrane permeation. These molecules exhibited high-affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…To synthesize MAP-Bicycle conjugates, different variants of a previously tested MAP (DRAMP18563 in Wagstaff et al , 2020) were generated with a C-terminal 3-azido- l -alanine (CAzal) group. A previously identified Bicycle molecule, which inhibits its periplasmic target (described previously as peptide 2 ) was also generated with a C-terminal Lys­(pentynoyl)-CONH ( AB1 ) . Copper­(I)-catalyzed azide–alkyne cycloaddition (CuAAC) was used to “click” the vector variant, with the Bicycle molecule generating the MAP-Bicycle conjugates (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To synthesize MAP-Bicycle conjugates, different variants of a previously tested MAP (DRAMP18563 in Wagstaff et al , 2020) were generated with a C-terminal 3-azido- l -alanine (CAzal) group. A previously identified Bicycle molecule, which inhibits its periplasmic target (described previously as peptide 2 ) was also generated with a C-terminal Lys­(pentynoyl)-CONH ( AB1 ) . Copper­(I)-catalyzed azide–alkyne cycloaddition (CuAAC) was used to “click” the vector variant, with the Bicycle molecule generating the MAP-Bicycle conjugates (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we conjugated a previously identified MAP to a Bicycle molecule selected against a periplasmic target and generated variations based on amino acid changes of the vector (Table ). The MAP-Bicycle conjugate shows enhanced antimicrobial activity compared to either the standalone vector or unconjugated Bicycle molecule, suggesting that MAP conjugation enhances OM penetration and delivery of the Bicycle molecule to its periplasmic target (Table , Figure A).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations